MEMBANGUN PEMAHAMAN KARAKTER KEJUJURAN MELALUI PERMAINAN TRADISIONAL PADA ANAK USIA DINI DI KOTA PATI - Lusiana, Ernita (Indonesian Journal of Early Childhood Education Studies, 2012)
Based on the data about the level of corruption case in Indonesia, the problem of corruption become the big problem which has to be solved. One of the alternative way is through the education. There is one value that is important to build the anti corruption character, it is the honesty value. The honesty value must be taught to the children since early. One of the media that can be used to implement the character education is through the method of children games. One of the games which can beused is traditional game which has developed in this country full of the countryâs culture. The aim of this research was to know whether the traditional game was effective or not to develop the childrenâs character in region of Pati. This research used experimental method, pretest and posttest control group design. The population was the institution of one foundation which aged 5-6. The sample was taken from the random sampling technique. The first sample as the experimental group from TKPertiwi 03 with 17 students. The second sample as the control group from TK Pertiwi 01 with 17 student. The analysis of t-test in posttest between the experimental group and control group, the result showed that t- count was 3.4897> t-table was 2.120. the score of sig (2-tailed) < 0.05, meant 0.01<0.05. It showed that Ho was rejected and Ha was accepted. The mean of posttest score improved from 40.1176 became 46.0588. The finding of the research showed that there was the difference understandingof honesty character between pretest and posttest result of experimental group, and there was not difference understanding of honesty character between pretest and posttest result of control group. It showed that the traditional game was effective to build the understanding of honesty character to the early childhood. This research was conducted based on the procedure of research, although there was limitation of the research. The limitation of time in the research. This research use the story test to know the honesty character of the children based on their answers, not from their behavior. It had better if this research also used the observation method. The limitation of the school yard, the wider school yard could make the traditional game effective to be played.